Between anarchy and tyranny: The republican meaning of the first political debate in Peru - Flores Camacho, Francisco Alejandro (2022)
The purpose of this article is to explore the first public discussion in the recently emancipated nation of Peru. The discussion about what would be the best form of government showed arguments in which its protagonists started from similar interpretations and, however, this did not lead to a similar proposal. The proposals differ by the main fears of the intellectuals: anarchy and tyranny. These are the two scenarios that monarchists and republicans will see with concern, although they will be inclined to give more importance to one of them. The article aims to put these concerns in the use of republican language, emphasizing the nuances that were used and returning to the thoughts of authors such as Cicero and Machiavelli.